PERAN LITERASI KEUANGAN DALAM KEPUTUSAN INVESTASI MAHASISWA PADA PASAR MODAL MELALUI GALERI INVESTASI FAKULTAS EKONOMI DAN BISNIS UNILAK - Rita Wiyati; Neneng Salmiah; Dwika Lodya Putri; Cindi Rahayu N; Devi Suprayogi (Komunitas Manajemen Kompetitif, 2026)
This study examines the role of financial literacy in shaping students’ investment decisions in the capital market through the Investment Gallery of the Faculty of Economics and Business, Universitas Lancang Kuning (FEB UNILAK). Although capital market education and facilities have been widely provided, students’ actual investment participation remains limited. This study employs a quantitative approach using a survey method. Primary data were collected from 115 students who had participated in capital market education programs and owned investment accounts. Data were analyzed using simple linear regression with SPSS software. The findings reveal that financial literacy plays a positive and statistically significant role in students’ investment decisions, explaining 69.5% of the variation in decision-making behavior. These results underline the importance of strengthening financial literacy to foster rational and informed investment decisions among university students.